Peak perihematomal edema expansion predicts poor outcome in patients with intracerebral hemorrhage - Sihui Wang; Xiaochen Wang; Xuening Zhao; Lingxu Chen; Shengjun Sun (Brain Hemorrhages)
Objective: Intracerebral hemorrhage (ICH) is a highly fatal and incapacitating form of stroke. Perihematomal edema (PHE) serves as a measurable radiological indicator in the progression of secondary injury and holds significant relevance in the assessment of disease outcome. Through a longitudinal cohort study, we examined the association between the expansion of peak PHE and functional outcome. Methods: We retrospectively enrolled supratentorial ICH patients with available computed tomography (CT) scans on admission within 6 h as well as day 1, day 8 ± 2, day 12 ± 2. Peak PHE expansion was defined as the the difference between maximum volume measured in any of the available CT scans and PHE volume on admission. We stratified patients into groups with unfavorable and favorable outcome, utilizing the modified Rankin Scale (mRS) score at the 90-day mark post-onset (with an mRS score ＞3 signifying an unfavorable outcome) Results: Eventually, a total of 140 patients were enrolled, and 84 patients (60 %) had poor outcome on day 90. Multivariable logistic regression revealed peak PHE expansion (OR 1.098 [95 % CI 1.049–1.150]) was independently associated with poor outcome. The best cutoff value was 12.8 ml with an AUC of 0.842. Conclusion: The peak PHE expansion correlates independently with adverse outcome for ICH patients within three months post-injury. It is anticipated that interventional therapies administered during the edema expansion phase could enhance the prognosis for ICH patients.